Early Balloon Kyphoplasty Treatment for Osteoporotic Vertebral Fracture Reduces Adjacent Vertebral Fractures - Hiromitsu Takano; Hidetoshi Nojiri; Arihisa Shimura; Juri Teramoto; Yuta Sugawara; Muneaki Ishijima (Medicina, 2024)
Background and Objectives: This study retrospectively examined whether the incidence rates of adjacent vertebral fractures (AVFs) can be reduced through balloon kyphoplasty (BKP) for osteoporotic vertebral fractures (OVFs) in the early stages, when there is little vertebral height variation. Materials and Methods: A total of 95 patients (22 males, 73 females, mean age: 80.7 years) who had undergone BKP were divided into two groups: the Early group (underwent BKP within 2 weeks after injury, n = 62), and the Non-early group (underwent BKP > 2 weeks after injury, n = 33). The following data were analyzed: patient characteristics; fracture level; the presence of old vertebral fractures, posterior wall injury, and intravertebral cleft; duration of surgery; duration of hospitalization; cement volume; the occurrence of AVF; the timing of AVF occurrence; Numerical Rating Scale (NRS) scores at the preoperative, postoperative, and final follow-up assessments; posterior vertebral kyphosis angle of the affected vertebra on plain lateral X-ray; vertebral wedge ratio; local kyphotic angle; and changes in posterior vertebral kyphosis angle, vertebral wedge ratio, and local kyphotic angle between preoperative and postoperative assessments. The patients were divided based on the occurrence or non-occurrence of AVF after BKP: the Non-AVF group, in which AVF did not occur, and the AVF group, in which AVF occurred. Results: The incidence of AVF was 15.8% (15/95 patients), with a notably lower incidence rate in the Early group at 6.5% (4/62 patients) compared to the Non-early group at 33.3% (11/33 patients). NRS scores significantly improved in both groups at the postoperative assessment and final follow-up. The changes in posterior vertebral kyphosis angle and vertebral wedge ratio were significantly lower in the Early group. In the Non-AVF group, the time from injury to surgery was significantly shorter. Conclusions: The Early group had a significantly lower incidence of AVF. The time from injury to surgery was a risk factor for AVF occurrence, suggesting that early BKP is recommended.